Immunosuppressive Consequences of Radiotherapy and Chemotherapy in Patients with Acute Lymphoblastic Leukaemia. Issue 5863 (19th May 1973) - Campbell, A. C.; Hersey, P.; MacLennan, I. C. M.; Kay, H. E. M.; Pike, M. C.; ,
Abstract : Assays of lymphocyte subpopulations and function have been performed on patients with acute lymphoblastic leukaemia still in remission after 18 months' treatment. The patients were subjects of a trial of the value of craniospinal irradiation in the third month of treatment in preventing central nervous system relapse. Effects of both irradiation and chemotherapy were observed. Lymphopenia was much more marked in those patients who had received irradiation over a year previously. Assays of response to phytohaemagglutinin (P.H.A.) and staining for surface immunoglobulin indicated that this difference was due to a deficiency in thymus-dependent lymphocytes in the irradiated children. Chemotherapy had a particularly marked depressant effect on lymphocytes with antibody-dependent cytotoxic activity and a proportion of PHA-responsive cells were also depressed. It may be relevant that four of the patients depleted of thymus-dependent lymphocytes by radiation died of infection during remission, while none of those treated with chemotherapy alone died in remission.